Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867) - Amey, Andrew P.; Edwards, Danielle L. (Zootaxa, 2017)
The Dotted-Line Robust Slider, Lerista lineopunctulata (Duméril & Bibron, 1839), is widely distributed along the western coast of Western Australia. An investigation of diversity within this taxon showed a clear split between northern and southern populations in the vicinity of Jurien. Accordingly, Lerista lineopunctulata is restricted to the southern population while the northern is recognised as Lerista miopus (Günther, 1867). Both taxa are redescribed and diagnosed and a neotype for L. miopus is designated.